BUZZ GROUP DALAM MENINGKATKAN PENGETAHUAN DAN SIKAP REMAJA DALAM PENCEGAHAN KEHAMILAN TIDAK DIINGINKAN (KTD) - Sofiana Salim; Abu Bakar; Retnayu Pradanie (Universitas Airlangga, 2014)
Unwanted pregnancy is unintended pregnancy by one or both prospective of infant's parents. Lack of knowledge about process and prevention of pregnancy are the major cause of unwanted pregnancy on adolescents. This study aimed to analyze buzz group effect on the adolescent's knowledge and attitude about prevention of unwanted pregnancy at SMK Muhammadiyah 3 Tegaldlimo Banyuwangi.This study used quasi-experimental design and population were all of class X at SMK Muhammadiyah 3 Tegaldlimo Banyuwangi. The sampling used purposive sampling technique, based on inclusion criteria, 20 repondents consisted of 16 repondents as experiments group and 16 respondents as control group. Data were collected by questionnaires and analyzed using Wilcoxon signed rank test and Mann Witney U Test with significant level α≤0,05. The results statistically showed that there were effect of buzz group on adolescent's knowledge (p=0.001) and attitude (p=0.005). There was difference between experiment group and control group after given buzz group on knowledge variable (p=0.000) and attitude variable (p=0.029). In conclusion, buzz group is an effective method of health education in providing information on prevention of unwanted preganancy in adolescent groups. Recommended for further research to analyze factors that effect adolescent's knowledge and attitude about prevention of unwanted pregnancy and study the effect of buzz group on behavior on adolescents